Penguatan Kewirausahaan Siswa Madrasah melalui Pelatihan Diversifikasi Produk Olahan Ayam Bernilai Tambah - Eka Agustiani; Endang Astuti; Laila Wardani; Vina Aprianti (Fakultas Ekonomi dan Bisnis Universitas Mataram, 2026)
This community service activity aims to enhance the entrepreneurial competencies of madrasah students through training in value-added chicken product diversification. The participants were students of grades 10, 11, and 12 at Madrasah Aliyah Raudatusshibyan NW Belencong, and the method applied was participatory training consisting of preparation, implementation, mentoring, and evaluation stages. The training focused on producing processed chicken products such as chicken siomay and chicken dumplings, along with basic entrepreneurial skills including packaging and simple marketing. Data were collected through observation, questionnaires, and pre-test and post-test to measure knowledge improvement. The results showed an increase in students’ entrepreneurial knowledge, product processing skills, and interest in entrepreneurship, with participants able to produce marketable products of fairly good quality in terms of taste and presentation. In addition, practice-based training proved effective in enhancing students’ confidence to start simple businesses, indicating that this program can be a strategic effort to strengthen entrepreneurship and promote economic independence within the school environment.